Emulsification and analyzing of oil in water emulsion by implementation of image processing method. (1st November 2016) - Azizi, K.; Nikazar, M.
ABSTRACT: Although a considerable amount of work has been done on emulsions, particularly regarding their relative stability, it is hard to find a method giving us an overall view about the amount of internal phase (AIP) in emulsions. Discussing this method and putting forward a way to evaluate these parameters is the aim of this paper. In this paper, image processing method is applied to quantify "Amount of Internal phase" in an emulsion. AIP is the parameter that shows the ratio of dispersed phase to the sum of internal and external phases of an emulsion. Microscopic observations of emulsions are fed into a program provided using MATLAB to compute AIP. A series of experiments have been carried out and chemical oxygen demand, COD, is used as a verification parameter. Results derived from image processing and COD tests are in agreement with each other and altogether showed that image processing will be able to be applied as a powerful tool in various applications of emulsions.